Ending the HIV epidemic PrEP equity recommendations from a rapid ethnographic assessment of multilevel PrEP use determinants among young Black gay and bisexual men in Atlanta, GA - Hill, Miranda; Smith, Justin; Elimam, Dena; Mustafaa, Genetha; Wortley, Pascale; Taylor, Brittany; Harris, Orlando (PloS one, 2023)
Efforts to mitigate HIV transmission among gay and bisexual men have not been sufficient to level persistent racial inequities which now extend to the use of daily oral pre-exposure prophylaxis (PrEP) for HIV prevention. Community-involved ethnographic research is crucial to galvanizing collaboration between patients, researchers, and policymakers to identify the social determinants of emerging PrEP inequities. In partnership with community key informants, we conducted a Rapid Ethnographic Assessment (REA) of multilevel PrEP use determinants among young Black gay and bisexual (YBGBM) men in the metropolitan Atlanta area to inform the development and coordination of local HIV programs. In the assessment, we drew upon the perspectives of local clinicians, community-based organization leaders, health educators, and PrEP clients to identify barriers and facilitators to PrEP use among YBGBM through interviews (N = 23). Data were collected from September 2020 -to January 2021 and were analyzed through a staged deductive-inductive thematic analysis. The themes were later summarized and presented to community stakeholder participants to facilitate member-checking. Our analyses revealed structural, cultural, relationship, and developmental factors which shaped PrEP use. The most prominent being "ease of access to PrEP" (structural level), "provider support" (interpersonal), and "life-stage traits" (individual). Our results also contribute novel information concerning the axes of intersectional stigma (spatial, racial, sexual identity, and HIV) among YBGBM in Atlanta and its divergent effects on PrEP use. Increased PrEP use among YBGBM, particularly among those living in the south, is essential to ending the domestic HIV epidemic. Altogether, our results emphasize the need for PrEP program modifications, which increase flexibility in methods and modes of access and are culturally adapted to the needs of YBGBM. There is also a need for resources that holistically focus on mental health, trauma, and racism as critical components of support.